2020
DOI: 10.1001/jamanetworkopen.2020.14780
|View full text |Cite
|
Sign up to set email alerts
|

Incidence of Stress Cardiomyopathy During the Coronavirus Disease 2019 Pandemic

Abstract: Key Points Question Is psychological, social, and economic stress associated with coronavirus disease 2019 (COVID-19) associated with the incidence of stress cardiomyopathy? Findings This cohort study included 1914 patients with acute coronary syndrome to compare patients presenting during the COVID-19 pandemic with patients presenting across 4 timelines prior to the pandemic and found a significantly increased incidence of 7.8% of stress cardiomyopathy dur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
187
2
11

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(221 citation statements)
references
References 10 publications
2
187
2
11
Order By: Relevance
“…In patients with myocarditis or inflammatory cardiomyopathies, inflammation is the primary cause of heart failure [5]. Moreover, cytokine-mediated inflammation has been implicated in acute stress-induced cardiomyopathy [6], an enigmatic entity that may be associated with major emotional or physical stress [7], and may also be a rare cause of myocardial injury in patients with coronavirus disease 2019 (COVID-19) [8,9]. In most other cases, activation of an inflammatory program reflects a reparative or protective response to other primary injurious processes.…”
Section: Introductionmentioning
confidence: 99%
“…In patients with myocarditis or inflammatory cardiomyopathies, inflammation is the primary cause of heart failure [5]. Moreover, cytokine-mediated inflammation has been implicated in acute stress-induced cardiomyopathy [6], an enigmatic entity that may be associated with major emotional or physical stress [7], and may also be a rare cause of myocardial injury in patients with coronavirus disease 2019 (COVID-19) [8,9]. In most other cases, activation of an inflammatory program reflects a reparative or protective response to other primary injurious processes.…”
Section: Introductionmentioning
confidence: 99%
“…Similar to cancer, COVID-19 causes significant emotional and physical stress to affected individuals. A retrospective study of 1914 patients by Jabri et al reported a significant increase in the incidence of SCM during the COVID-19 period compared with the pre-pandemic time (7.8% vs 1.5-1.8%, respectively, p < 0.001) [43]. Although there is no published data at the time of this review regarding the incidence of SCM in patients with cancer and COVID-19, it is suspected to be increased due to the combination of these two risk factors.…”
Section: Stress Cardiomyopathy In Patients With Covid-19 and Cancermentioning
confidence: 99%
“…19,20 An increased incidence of stress/Takotsubo cardiomyopathy (TCM) had been found in a cohort study of 1914 patients who presented with acute coronary syndrome during the COVID-19 pandemic as compared with the prepandemic period. 21 New onset cardiomyopathy has also been demonstrated in 33% of nonpregnant COVID-19 patients who required intensive care. 22 Viral genome has also been demonstrated in myocardial tissue of such patients in one study.…”
Section: Peripartum Cardiomyopathy In Pregnancy With Covid-19mentioning
confidence: 99%